FACING THE DIGITAL ERA: A COMPREHENSIVE TRANSFORMATION OF MADRASAS THROUGH TECHNOLOGY - Risqah Amaliah Kasman; H. Suhada; Ulfah Umurohmi; Mohammad Ahmad Bani Amer (Indonesian Journal of Education (INJOE), 2024)
In an era increasingly dominated by digital technology, the education sector faces the challenge of adapting and utilizing technology to enrich the learning process. This study aims to analyze how madrasahs in Indonesia respond to and implement digital transformation in their educational activities. The research method used is a literature study, where data and information are collected from various sources such as relevant journals, articles, and research reports to find out the best practices and challenges in digital transformation in madrasahs. The results show that madrasahs have adapted technology in their curriculum and teaching methodology, including the use of digital tools in the teaching and learning process, the development of digital competencies for teachers and students, and the implementation of online learning management systems. However, significant challenges were observed in terms of resource availability, such as limited access to adequate technological devices and digital learning materials, as well as the need for teacher training to maximize the use of technology in education